2008
DOI: 10.1111/j.1538-7836.2008.03037.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of fractional synthesis rate (FSR) of fibrinogen, concentration of D‐dimer and fibrinolytic balance to physical activity‐based intervention in obese children

Abstract: Summary. Background: Physical activity-induced reduction in obesity-related hyperfibrinogenemia in children has been reported. The underlying mechanisms remain elusive. Further, the effect of such interventions on fibrinolysis in children is scarce. Objectives: To investigate in obese children, before and after a physical activity-based intervention: (i) the mechanistic role of fractional synthesis rate (FSR) of fibrinogen in the reduction of hyperfibrinogenemia; and (ii) the changes in fibrinolytic factors. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
2
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 47 publications
(84 reference statements)
2
28
2
1
Order By: Relevance
“…Fibrinogen promotes fibrin formation and is as important a risk factor for coronary heart disease as cigarette smoking, cholesterol level, and hypertension (22,23,28). Fibrinogen concentrations are correlated with adiposity in children (25), likely secondary to an increase in the fractional synthesis rate of fibrinogen (39,40). The adipocyte produces PAI-1, the principal physiological inhibitor of fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen promotes fibrin formation and is as important a risk factor for coronary heart disease as cigarette smoking, cholesterol level, and hypertension (22,23,28). Fibrinogen concentrations are correlated with adiposity in children (25), likely secondary to an increase in the fractional synthesis rate of fibrinogen (39,40). The adipocyte produces PAI-1, the principal physiological inhibitor of fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
“…245 The role of fibrinogen fractional synthesis rate remains to be fully understood. A few studies have also shown elevated levels of D-dimer in obese versus lean children, 92,120,246, and high levels of tPA and PAI-1 have been reported in obese children, 93,116,120,246 reflecting impairment of the fibrinolytic system. The molar ratio of PAI-1 to tPA, often considered an index of vascular fibrinolytic balance, 94 was found to be higher in obese children compared with lean control subjects in 1 study.…”
Section: Hemostasis and Thrombosismentioning
confidence: 99%
“…The molar ratio of PAI-1 to tPA, often considered an index of vascular fibrinolytic balance, 94 was found to be higher in obese children compared with lean control subjects in 1 study. 120 Physical activity-based interventions in children have shown consistent decreases in the levels of fibrinogen and D-dimer. 56,89,96 -99,120 -123,246,231 The effect on levels of PAI-1 and the fibrinolytic system, on the other hand are mixed.…”
Section: Hemostasis and Thrombosismentioning
confidence: 99%
“…In a smaller study lasting three months in duration, a program of combined behavioral, nutritional and aerobic exercise (walking) resulted in only a small reduction in BMI in obese adolescents but led to significant reductions in several inflammatory markers, the concentration and synthesis rate of fibrinogen, and the concentration of the fibrin split product, D-dimer. 24,25 These findings suggest that thrombotic risk, which is increased in obese children, is reduced following a relatively short intervention period with modest changes in behavior.…”
Section: Dovepressmentioning
confidence: 87%
“…18 Obese children routinely have been shown to have many of the proinflammatory, proathrogenic changes associated with vascular disease in adults, including insulin resistance, hepatic steatosis, elevated total-, low-density lipoprotein-cholesterol (LDL-C), and oxidized LDL-C, elevated levels of vascular adhesion molecules, tumor necrosis factor-α (TNF-α), C-reactive protein, interleukin-6 (IL-6), and fibrinogen, while high-density lipoprotein-cholesterol (HDL-C) and adiponectin are reduced. [19][20][21][22][23][24][25][26][27][28] These deleterious changes set the stage of early development of vascular dysfunction and atherosclerosis. Most concerning is the evidence that these risk factors are fairly stable in adolescents if body mass index (BMI) is unchanged 29 and track from adolescence into adulthood.…”
Section: Dovepressmentioning
confidence: 99%